Sams teach yourself Visual Basic 6 in 24 hours - Perry, Greg M. (Sams, 1998)
Teach Yourself Visual Basic 6 in 24 Hours follows the step-by-step approach of the Teach Yourself series and gives the reader a quick, concise introduction to this programming language. It will explain the basics of Visual Basic through task-oriented examples and a hands on approach. Topics covered include: Basics of Visual Basic development, Understanding the concepts of properties, methods, and events, Creating and implementing ActiveX controls, Integrating data into applications, Adding and manipulating graphics, Testing and debugging applications, Printing from your applications.